Characteristics, Trends, and Outcomes of Liver Transplantation for Primary Sclerosing Cholangitis in Female Versus Male Patients: An Analysis From the European Liver Transplant Registry. Issue 10 (1st October 2021) - Berenguer, Marina; Di Maira, Tommaso; Baumann, Ulrich; Mirza, Darius F.; Heneghan, Michael A.; Klempnauer, Jurgen L.; Bennet, William; Ericzon, Bo-Goran; Line, Pål-Dag; Lodge, Peter A.; Zieniewicz, Krzysztof; Watson, Christopher J. E.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The influence of sex on primary sclerosing cholangitis (PSC), pre- and postliver transplantation (LT) is unclear. Aims are to assess whether there have been changes in incidence, profile, and outcome in LT-PSC patients in Europe with specific emphasis on sex. Methods: Analysis of the European Liver Transplant Registry database (PSC patients registered before 2018), including baseline demographics, donor, biochemical, and clinical data at LT, immunosuppression, and outcome. Results: European Liver Transplant Registry analysis (n = 6463, 32% female individuals) demonstrated an increasing number by cohort (1980–1989, n = 159; 1990–1999, n = 1282; 2000–2009, n = 2316; 2010–2017, n = 2549) representing on average 4% of all transplant indications. This increase was more pronounced in women (from 1.8% in the first cohort to 4.3% in the last cohort). Graft survival rate at 1, 5, 10, 15, 20, and 30 y was 83.6%, 70.8%, 57.7%, 44.9%, 30.8%, and 11.6%, respectively. Variables independently associated with worse survival were male sex, donor and recipient age, cholangiocarcinoma at LT, nondonation after brain death donor, and reduced size of the graft. These findings were confirmed using a more recent LT population closer to the current standard of care (LT after the y 2000). Conclusions: An increasing number of PSC patients, particularly women, are being transplanted in European countries with better graft outcomes in female recipients. Other variables impacting outcome include donor and recipient age, cholangiocarcinoma, nondonation after brain death donor, and reduced graft size. Abstract :